2013
DOI: 10.1104/pp.113.217869
|View full text |Cite
|
Sign up to set email alerts
|

A Guanine Nucleotide Exchange Factor for Rab5 Proteins Is Essential for Intracellular Transport of the Proglutelin from the Golgi Apparatus to the Protein Storage Vacuole in Rice Endosperm      

Abstract: Rice (Oryza sativa) glutelins are synthesized on the endoplasmic reticulum as a precursor, which are then transported via the Golgi to protein storage vacuoles (PSVs), where they are proteolytically processed into acidic and basic subunits. The glutelin precursor mutant6 (glup6) accumulates abnormally large amounts of proglutelin. Map-base cloning studies showed that glup6 was a loss-offunction mutant of guanine nucleotide exchange factor (GEF), which activates Rab GTPase, a key regulator of membrane trafficki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 45 publications
2
50
0
2
Order By: Relevance
“…For example, the esp2/pdi1-1 mutant forms small PBIs, W379/vpe1 develops round PBIIs (Wang et al, 2009), while gpa3 contains normal PBIs but small PBIIs. The observed gpa3 mutant phenotypes and subcellular defects are most reminiscent of the recently reported glup4/gpa1/rab5a and glup6/gpa2/vps9a mutants (Wang et al, 2010;Fukuda et al, 2011Fukuda et al, , 2013Liu et al, 2013). However, the defects in gpa3 appeared to be more severe than those observed in glup4/gpa1/rab5a and glup6/gpa2/ vps9a (Figure 7).…”
Section: Discussion Gpa3 Is Defective In Post-golgi Trafficking Of Stsupporting
confidence: 78%
See 2 more Smart Citations
“…For example, the esp2/pdi1-1 mutant forms small PBIs, W379/vpe1 develops round PBIIs (Wang et al, 2009), while gpa3 contains normal PBIs but small PBIIs. The observed gpa3 mutant phenotypes and subcellular defects are most reminiscent of the recently reported glup4/gpa1/rab5a and glup6/gpa2/vps9a mutants (Wang et al, 2010;Fukuda et al, 2011Fukuda et al, , 2013Liu et al, 2013). However, the defects in gpa3 appeared to be more severe than those observed in glup4/gpa1/rab5a and glup6/gpa2/ vps9a (Figure 7).…”
Section: Discussion Gpa3 Is Defective In Post-golgi Trafficking Of Stsupporting
confidence: 78%
“…It has been reported that loss of function of rice GLUP4/GPA1/ Rab5a results in partial secretion of proglutelins and a-globulins to the extracellular space (Wang et al, 2010;Fukuda et al, 2011). Recently, rice VPS9a has also been identified to be the GEF of Rab5a, and its loss-of-function mutant gpa2/glup6 displays similar but more severe phenotypic defects than glup4/gpa1/ rab5a (Fukuda et al, 2013;Liu et al, 2013). These observations support a role for Rab5a and VPS9a in the transport of proglutelins from the Golgi apparatus to PSV.…”
Section: Gpa3mentioning
confidence: 99%
See 1 more Smart Citation
“…The w379/glup3 mutants, both resulting from mutation of VPE1, develop round-shaped PBII (Wang et al, 2009;Kumamaru et al, 2010). The other three mutants defective in post-Golgi trafficking, gpa1/glup4/rab5a, gpa2/glup6/vps9a, and gpa3, all develop large amounts of protein granules and paramural bodies in the apoplast (Wang et al, 2010;Fukuda et al, 2011Fukuda et al, , 2013Liu et al, 2013;Ren et al, 2014). Moreover, PDIL1-1 functions in the ER lumen, and VPE1 plays a role in PSV/PBII, while GPA1, GPA2, and GPA3 form a complex that is present in the trans-Golgi networks and prevacuolar compartments.…”
Section: Discussion Gpa4 Is Defective In Storage Protein Exit From Thmentioning
confidence: 99%
“…Any defects in the proglutelin trafficking process before reaching the PBII can lead to overaccumulation of the 57-kD precursor proteins (referred to as the 57H phenotype) in the seeds. Through the studies of 57H mutants, several key factors involved in post-Golgi trafficking of storage proteins have been characterized (Wang et al, 2010;Fukuda et al, 2011Fukuda et al, , 2013Liu et al, 2013;Ren et al, 2014). However, how these storage proteins are first exported from the ER remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%